2018
DOI: 10.1111/iju.13721
|View full text |Cite
|
Sign up to set email alerts
|

Combination of solifenacin with tamsulosin reduces prostate volume and vascularity as opposed to tamsulosin monotherapy in patients with benign prostate enlargement and overactive bladder symptoms: Results from a randomized pilot study

Abstract: The results of this pilot study suggest that solifenacin might affect morphometric properties of the prostate, decreasing total prostate and adenoma volume, as well as vascularity. A molecular effect of antimuscarinics on the prostate, in parallel with their expected bladder effect, warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Lower urinary tract symptoms (LUTS) are among the most common urologic conditions in the older population . As the incidence of LUTS and frailty increases with age, the concept of frailty has been recognized as a key factor in older individuals with LUTS . However, only a few studies have evaluated the influence of frailty on LUTS .…”
Section: Introductionmentioning
confidence: 99%
“…Lower urinary tract symptoms (LUTS) are among the most common urologic conditions in the older population . As the incidence of LUTS and frailty increases with age, the concept of frailty has been recognized as a key factor in older individuals with LUTS . However, only a few studies have evaluated the influence of frailty on LUTS .…”
Section: Introductionmentioning
confidence: 99%
“…The non-DO monotherapy subgroup showed comparable efficacy to the non-DO combination treatment subgroup in improving nocturia episodes (P = 0.599). In the analysis of unstratified data, nocturia episodes were reduced in both treatment arms, with near-statistical significance for the combination treatment (monotherapy, -1.5 vs. combination, -2.0, P = 0.057) [14]. Fig.…”
Section: Injmentioning
confidence: 81%
“…The non-DO monotherapy subgroup showed comparable efficacy to the non-DO combination treatment subgroup in terms of improvements in urgency episodes (P = 0.126). In the initial study, both treatment groups showed improvements in urgency episodes as compared to baseline (monotherapy, -3.0 vs. combination, -3.5; P < 0.001), and the intergroup comparison did not reveal any significant differences [14]. Nocturia also improved in men with DO who received combination treatment as compared to the DO monotherapy subgroup (P = 0.018), to the non-DO combination treatment subgroup (P = 0.03), and to the non-DO monotherapy subgroup (P = 0.037).…”
Section: Injmentioning
confidence: 85%
See 2 more Smart Citations